Storyworlds: voyage into space - Edmonds, William (Heinemann UK, 2009)
"Voyage into Space" is an exciting story that takes readers on a journey through the cosmos, exploring planets, stars, and galaxies. It sparks curiosity about space, technology, and the wonders of the universe.